2023
DOI: 10.1051/e3sconf/202337101032
|View full text |Cite
|
Sign up to set email alerts
|

Invitro rearing of parasitoids

Abstract: Since 2015, the studies on in vitro rearing Braconidae and Trichogrammatidae (B. habetor Say, B. greeni and T. pintoe, T. evanescens, T. chilonis) have been conducted successfully in Uzbekistan. For these parasites, cooking and the three main types of media were made from the hemolymph of the wax moth (G. melonnella) and cotton worm Helicoverpa armigera (Heliothis armigera), egg yolk, natural milk 10%. The simulated "host-eggs" and "larvae" are made of polyethylene or polypropylene semi spherical capsules, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…In the conditions of the Bukhara province, the average air temperature during the year is +14.2 o C +18.0 o C. The hottest air temperature is observed in July of the year with an average of +28.3 o C; +29.6 o C, and the cooling of the temperature was recorded in January, the air temperature was +1.5 o C; -0.4 o C. Atmospheric precipitation averages around 114-205 mm, and precipitation falls mainly in the winter-spring seasons of the year. The average air humidity is 51-55%, and in summer it is 17-25% [12,13]. Studies have been conducted (2018-2021) in the arable layer (0-30 cm) of the meadow alluvial soils of Bukhara district, the amount of humus is on average 1.20%, and in the subarable layer (30-50 cm) it is on average 0.56%, total nitrogen is 0.092-0.051 %, phosphorus 0.24-0.16%, potassium 1.56-1.03%, mobile nitrogen 14.61-7.52 mg/kg, mobile phosphorus 31.26-23.21 mg/kg, and mobile potassium was 240.41-170.31 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…In the conditions of the Bukhara province, the average air temperature during the year is +14.2 o C +18.0 o C. The hottest air temperature is observed in July of the year with an average of +28.3 o C; +29.6 o C, and the cooling of the temperature was recorded in January, the air temperature was +1.5 o C; -0.4 o C. Atmospheric precipitation averages around 114-205 mm, and precipitation falls mainly in the winter-spring seasons of the year. The average air humidity is 51-55%, and in summer it is 17-25% [12,13]. Studies have been conducted (2018-2021) in the arable layer (0-30 cm) of the meadow alluvial soils of Bukhara district, the amount of humus is on average 1.20%, and in the subarable layer (30-50 cm) it is on average 0.56%, total nitrogen is 0.092-0.051 %, phosphorus 0.24-0.16%, potassium 1.56-1.03%, mobile nitrogen 14.61-7.52 mg/kg, mobile phosphorus 31.26-23.21 mg/kg, and mobile potassium was 240.41-170.31 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Providing context to the scale of the weed challenge, research conducted in Russia reveals that agricultural fields harbor an astonishing average of 100 million to 3-4 billion weed seeds per hectare. This statistic emphasizes the pervasive nature of weed proliferation, necessitating comprehensive and proactive measures to manage and mitigate their impact on crop growth and yields [10][11][12][13][14]. Implementing sustainable weed control practices becomes essential not only for preserving the nutritional integrity of cultivated crops but also for securing the economic viability of agriculture on a broader scale.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, $85 million worth of wheat was sold in Alabama. Here, it was found that the reason for the higher yield than wheat was that the legume srotalaria juncea was planted in these fields before wheat [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%